2020
DOI: 10.21608/ejss.2020.33931.1365
|View full text |Cite
|
Sign up to set email alerts
|

Land Resources Evaluation for Sustainable Agriculture in El-Qusiya Area, Assiut, Egypt

Abstract: I NCREASING the cultivated areas in Egypt is necessary to achieve over-growing population sufficiency. However, accurate land evaluation is great concern to achieve sustainable agricultural production. The current study aimed at evaluating land capability and suitability in El-Qusiya City, Assiut Governorate, Egypt using Remote Sensing (RS) and Geographic Information Systems (GIS) techniques. The soils of the study area belonged two land capability classes according to Storie index; fair (Grade 3) that occupie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…To evaluate the quality of our natural resources and their potential to produce food, fodder, fiber, and fuel for the present and future generations, detailed information on soil properties is needed. Accurate land evaluation is a great concern to achieve sustainable agricultural production (Fadl and Sayed, 2020). Moreover, understanding soil properties and their distribution over an area are useful for sustainable development and the efficient use of limited land resources (Sanchez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the quality of our natural resources and their potential to produce food, fodder, fiber, and fuel for the present and future generations, detailed information on soil properties is needed. Accurate land evaluation is a great concern to achieve sustainable agricultural production (Fadl and Sayed, 2020). Moreover, understanding soil properties and their distribution over an area are useful for sustainable development and the efficient use of limited land resources (Sanchez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the study area was not suitable for citrus and onion, moderately suitable for growing maize, and highly suitable for barley, date palm and wheat. Land suitability varied from one region to another, with some areas being very suitable while others were moderately suitable or marginally suitable (Fadl and Sayed, (2020) and Jalhoum et al (2022). The major goals of this study were to assess the soil fertility of some soils in Egypt's Samannoud District, Gharbia Governorate and determine whether they were suitable for a few critical crops using the ASLE program and GIS techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Sayed and Khalafalla (2021) used GIS techniques for land evaluation of some soils in Northwest of Dashlut, Assiut, Egypt. The same techniques were used for the same purpose in Eastern Sohag (Moursy et al, 2020), Tushka area (Abd El-Aziz, 2018), Southwest of Aswan city (Aldabaa and Yousif, 2020), ElQusiya Area, Assiut (Fadl and Sayed, 2020), and Bahariya Oasis (Shokr et al, 2022).…”
Section: Introductionmentioning
confidence: 99%